Economic and Social Drivers of Scientific Productivity in Latin America: Evidence from a Panel Quantile Regression - Tenesaca, Kleber; Benítez, Segundo; Torres, Viviana; Quito, Byron; Ojeda, Cristian; Ochoa-Moreno, Santiago (Journal of Posthumanism, 2025)
The scientific production of a country drives economic, technological, and social development by generating knowledge, fostering innovation, and enhancing competitiveness. It also contributes to addressing global challenges and strengthening both education systems and international cooperation. Given its impact on national sustainability and progress, this study analyzes the influence of key variables-globalization, civil liberties, R&D expenditure, and GDP per capita-on the volume of scientific publications across 15 Latin American countries between 2001 and 2019, using the panel quantile regression method. The findings reveal that scientific production, measured by the number of published articles, is positively influenced by GDP per capita, globalization, and civil liberties. Furthermore, the study highlights the importance of R&D expenditure, both public and private, in knowledge generation. This research suggests that policymakers should promote economic development through the region’s scientific capabilities to foster sustainable development and technological progress in Latin America.